(untitled) (Proceedings of the Mongolian Academy of Sciences, 2019)
Heterodermia hypoleuca (Ach.) Treis.,H. japonica (M. Sato) Swinscow & Krogand H. subascendens (Asahina) Trass. have been recorded for the first time in Mongolia. Data on substrates, habitats, distribution are listed for every species. Taxonomic comments and distinctive characters are provided for these species. The habitats are briefly described and the frequently associated species are listed. It is interesting to note that as a result of processing hundreds of herbarium collections of lichens, numerous new species were found in Mongolia. This means that there is still a substantial gap in the knowledge, especially about the lichen flora of remote corners of the country, which are numerous.